Historical violence and public attitudes towards justice: evidence from the United States - Scott, Jamil (International journal of transitional justice, 2024)
This article brings transitional justice scholarship to bear on the case of racial violence in the United States. We investigate how knowledge of racial terror lynchings shapes Black Americans’ support for symbolic and material transitional justice measures. We administer a survey with an embedded experiment to Black residents in Maryland, a US transitional justice pioneer. We provide select respondents with information about historical lynching violence and find that they are more likely to support symbolic transitional justice (e.g., apologies and memorial markers) than individuals presented with information on contemporary police killings. Regarding material transitional justice (e.g., monetary reparations and community projects), we find no significant differences between groups. Linked fate excepted, we do not find that key aspects of Black identity and the Black American experience (i.e., historical knowledge, police contact, church involvement and Black nationalist beliefs) moderate transitional justice attitudes. Our work indicates the promise and limits of information campaigns to mobilize support for transitional justice.